Comprehensive Strategic Analysis for Determining Strategic Policies at Pt. Lmc - Matias Andika Yuwono; Lena Ellitan (International Journal of Management, Accounting and Economics)
This article aims to explain the processes carried out by management at PT. LMC is used to determine company strategy for partnership activities. Several analyses are carried out to determine the company's strategy, such as market analysis, industry analysis, company analysis, SWOT analysis, and risk analysis. After conducting various analyses, company management can formulate a strategic plan, determine a partnership strategy model, and implement the strategy that has been chosen while still paying attention to possible risks. This research uses a qualitative analysis approach with a case study method. By conducting a comprehensive analysis, the management of PT. LMC can determine strategic plans effectively and implement partnership programs consistently while minimizing possible risks. Apart from that, the partnership operational division can carry out the strategy in stages with clear goals and targets to be more efficient. Management can continue to carry out regular monitoring activities to see whether the partnership program is still running well and making a contribution to the company. This article discusses the process of determining company strategy based on comprehensive analysis, which combines several analyses so that management can evaluate policies and supervise them effectively.